Precise Synthesis of High-Strength Chiral Au Nanomaterials: From Chiral Au Nanoclusters to Chiral Au Nanoparticles - Haijuan Luo; Chuanhua Shi; Zhixun Zhang; Yan Nong; Juefei Dai; Chengcheng Feng; Wenjie Li; Xianyong Yu; Xueji Zhang; Huayan Yang (Inorganics)
Chiral gold nanomaterials have promising applications in biomedicine, catalysis, optics and other fields. However, the complexity of their chiral sources has led to many challenges in terms of the functional design and controlled synthesis. In this paper, we systematically review the development history of chiral Au nanomaterials; deeply analyze the synthesis strategy, chiral construction mechanism, and performance optimization pathway; and discuss the formation mechanism in light of the progress of cutting-edge research to look into the future direction of development. The aim is to provide theoretical and methodological support for the controllable synthesis of chiral gold nanomaterials.